Errata - Editorial, Errata (South African Journal of Enology and Viticulture, 2017)
Myburgh, P.A., 2003. Responses of Vitis vinifera L. cv. Sultanina to water deficits during vatious pre- and post-harvest phases under semi-arid conditions. S. Afr. J. Enol. Vitic. 24, 25-33. Table 4 on page 30 must be replaced